(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article presents the results of theoretical prerequisites and the results of a study of the possibility of developing new teaching methods, using the theory of similarity based on everyday examples, especially for conducting classes in technical educational institutions.